Emerging Pollutants in the Environment - Current and Further Implications 2015
DOI: 10.5772/60216
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicological Threats of Pollutants in Aquatic Invertebrates

Abstract: Immunology deals with the physiological activity of organisms to defend against pathogen and toxin invasion. Invertebrates residing in aquatic ecosystems often face toxicological threat arises from habitat pollution. The aquatic habitat of invertebrates is in the precarious risk of pollution caused by diverse groups of environmental toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…The field of immunotoxicology in wildlife is relatively new, and there is scarce knowledge about this subject in reptiles (Siroski et al, 2016). Nevertheless, it has been reported that some pesticides affects defense mechanisms and can alter structures of some components of the IS (Ray et al, 2015). Thus, for example, some authors have reported effects of Roundup (RU, glyphosate-based formulation) on some parameters of the IS and growth of Caiman latirostris (Latorre et al, 2013;Siroski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The field of immunotoxicology in wildlife is relatively new, and there is scarce knowledge about this subject in reptiles (Siroski et al, 2016). Nevertheless, it has been reported that some pesticides affects defense mechanisms and can alter structures of some components of the IS (Ray et al, 2015). Thus, for example, some authors have reported effects of Roundup (RU, glyphosate-based formulation) on some parameters of the IS and growth of Caiman latirostris (Latorre et al, 2013;Siroski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…THC adalah total hemosit dalam tubuh gastropoda yang dapat digunakan sebagai biomarker dalam mendeskripsikan suatu status pencemaran lingkungan. Apabila terjadi suatu pencemaran, maka THC akan mengalami kenaikkan [30]. THC terdiri dari sel hyalinosit, semi granulosit, granulosit dan sel-sel yang mati [31].…”
Section: Thc (Total Haemocyte Count)unclassified
“…Immunotoxicants are environmental contaminants and drugs that disrupt the immune system’s balance and cause damage to living organisms 2 . Common environmental agents that contribute to immune deficiency are stress, some bacterial and fungal toxins, pesticides, alcohol and tobacco abuse, or pharmaceuticals such as antibiotics, chemotherapeutic agents, birth control pills, and neuropsychiatric drugs 3 4 5 .…”
Section: Introductionmentioning
confidence: 99%